Nutraceutical benefits of Salvia hispanica and its anti-oxidant and anti-microbial effects - Agarwala, Satyakam; Sharma, Deboja; Sanjrambam , Binapani (Journal of Postharvest Technology, 2023)
Chia seed is increasing in popularity as a nutritional rich diet and medicinal food. A native of Central and South Mexico, Chia seeds  are edible seeds of Salvia hispanica which is an annual flowering herbaceous plant belonging to the mint family (Lamiaceae). In recent years,  usage of chia seeds has tremendously grown due to their higher nutritional level and medicinal values. Chia was cultivated by Mesopotamian  cultures, but then disappeared until the middle of 20th century, when it was rediscovered in 1990s. Chia seeds contain healthy omega -3 fatty  acids, dietary fibres, proteins and vitamins and some minerals. Besides these the seeds are an excellent source of antioxidants. Today chia has  been analysed in different areas of research. Researchers have been investigating the benefits of chia seeds in medicinal, pharmaceuticals and  food industries. Chia oil is today one of the most valuable oils in the market. This study is aimed to characterize the chia seeds (Salvia hispanica),  get chia seed oil by different extraction methods and analyse their nutritional properties, antioxidant properties and antimicrobial properties.  By conducting and analysing the experiment it was found that chia seeds contain a good amount of antioxidant properties, contains  phytochemical compounds like alkaloid and flavonoid whereas terpens and tannins were found to be absent. It has also antimicrobial properties  in which E.coli, Klebseilla are found to be sensitive whereas Salmonella spp. was found to be resistant.
Keywords: Salvia hispanica; phytochemical; antioxidant,; antimicrobial